2015
DOI: 10.1111/pai.12358
|View full text |Cite
|
Sign up to set email alerts
|

Extended implementation of educational programs for atopic dermatitis in childhood

Abstract: Children with atopic dermatitis (AD) suffer from chronic relapsing inflammatory skin lesions accompanied by insatiable itching, dryness, excoriated skin, or even (super-)infections. This burden impairs the quality of life of affected children and their families. Due particularly to the recurrent course of the disease, patients often lose confidence in treatment and fear side effects of steroids. Family education programs for AD have been established in the last decades to provide appropriate education and psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
1
11
0
1
Order By: Relevance
“…The educational program—which aimed to empower the patient in a primary care setting—proved to be beneficial for drug prescription and the early recognition of exacerbated symptoms of asthma, amongst other things. This article confirms earlier reports in PAI which assessed the effectiveness of education in asthma and other related diseases such as atopic dermatitis and food allergy …”
supporting
confidence: 91%
See 1 more Smart Citation
“…The educational program—which aimed to empower the patient in a primary care setting—proved to be beneficial for drug prescription and the early recognition of exacerbated symptoms of asthma, amongst other things. This article confirms earlier reports in PAI which assessed the effectiveness of education in asthma and other related diseases such as atopic dermatitis and food allergy …”
supporting
confidence: 91%
“…This article confirms earlier reports in PAI which assessed the effectiveness of education in asthma 5 and other related diseases such as atopic dermatitis and food allergy. 6,7 Obesity as a risk factor and how it influences allergic diseases such as asthma has been shown earlier in PAI, 8,9 in particular how it affects hospital re-admission and length of stay. 10 Liu et al 11 have in this issue investigated a possible link between incidence and severity of allergic rhinitis and obesity, a closely related problem.…”
mentioning
confidence: 89%
“…TCS potency was not correlated with AD severity or QoL, whereas the number of different therapies and the total number of prescriptions were correlated, thus these last two parameters might serve as a measure for AD severity and AD‐related QoL. In addition, it seems that children with multiple atopic disorders experience AD as more impairing, thus interventions specifically targeted at this group might empower these children and improve QoL …”
Section: Resultsmentioning
confidence: 99%
“…In addition, it seems that children with multiple atopic disorders experience AD as more impairing, thus interventions specifically targeted at this group might empower these children and improve QoL. 25 What's already known about this topic?…”
Section: Discussionmentioning
confidence: 99%
“…Besides therapeutics and preventive measures, much attention is gathered around family educational programs for AD. Ahrens et al (27). reviewed existing educational strategies and concluded that there is enough evidence to integrate appropriate programs routinely into the treatment of AD children that will ultimately empower the affected child and its caregivers to obtain best possible care, prevention, and quality of life.…”
Section: Atopic Dermatitismentioning
confidence: 99%